Development and Evaluation of Leflunomide Nanoemulgel: A Novel Topical Delivery System for Treatment of Rheumatoid Arthritis - Sonu Choudhary,; Pradeep Pal,; Vikas Jain, (The Bioscan, 2025)
Background: Rheumatoid arthritis (RA) is a chronic inflammatory autoimmune disease characterized by persistent synovial inflammation, joint pain, and progressive cartilage destruction. Leflunomide, a widely used disease-modifying antirheumatic drug (DMARD), effectively suppresses T-cell proliferation by inhibiting dihydroorotate dehydrogenase. However, its oral administration is limited by poor aqueous solubility, first-pass hepatic metabolism, and systemic side effects including hepatotoxicity and gastrointestinal discomfort. These limitations necessitate the development of an alternative drug delivery approach that enhances local efficacy while reducing systemic exposure. Objective: The present study was undertaken to formulate and evaluate a leflunomide-loaded nanoemulgel for topical application to improve local anti-inflammatory activity, enhance drug permeation through the skin, and reduce adverse systemic effects in the management of rheumatoid arthritis. Methods: A nanoemulsion of leflunomide was prepared using oleic acid as the oil phase, Tween 80 as the surfactant, and propylene glycol as the co-surfactant via the spontaneous emulsification technique. The optimized nanoemulsion was then incorporated into a Carbopol 940 hydrogel base, and phenoxyethanol was used as a preservative. The nanoemulgel was evaluated for various physicochemical properties, including droplet size, polydispersity index (PDI), zeta potential, pH, viscosity, spreadability, and drug content. In-vitro drug release studies were performed using Franz diffusion cells over a 24-hour period and compared to a conventional leflunomide gel. Results: The optimized nanoemulgel exhibited a mean droplet size below 200 nm, low PDI (< 0.3), and a stable zeta potential, indicating good formulation stability. The pH and viscosity were within acceptable limits for dermal application, and the formulation showed excellent spreadability and over 95% drug content uniformity. In-vitro release studies demonstrated 74% cumulative drug release over 24 hours from the nanoemulgel, significantly higher than the conventional gel, confirming improved release and potential for enhanced topical efficacy. Conclusion: The developed leflunomide-loaded nanoemulgel, comprising oleic acid, Tween 80, propylene glycol, and phenoxyethanol, showed promising physicochemical characteristics and superior drug release behavior. These findings support its potential as an effective and safe topical therapeutic system for the localized treatment of rheumatoid arthritis.